Impurity analysis method and chemical container used therefor

The impurity analysis method using a chemical container with an etching solution allows for non-destructive analysis of silica glass crucibles, addressing the challenges of contamination and inaccuracy in existing methods by controlling diffusion and ensuring precise impurity determination.

JP7602369B2Active Publication Date: 2024-12-18MOMENTIVE TECH YAMAGATA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020214183
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-23
Publication Date
2024-12-18
Estimated Expiration
2040-12-23

AI Technical Summary

Technical Problem

Existing methods for analyzing impurities on the outer surface of silica glass crucibles used in silicon single crystal pulling are non-destructive and prone to contamination, especially due to the use of hydrofluoric acid vapor and etching solutions, which are difficult to apply and can lead to inaccurate results.

Method used

An impurity analysis method using an etching solution contained in a chemical container that protrudes from its upper end to dissolve the outer surface of the crucible, allowing for non-destructive analysis by pressing against the surface and collecting the dissolved solution for analysis.

Benefits of technology

Enables non-destructive analysis of impurities on the outer surface of silica glass crucibles, ensuring high purity by controlling diffusion and facilitating accurate determination of impurity concentrations without damaging the crucible.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602369000003
    Figure 0007602369000003
  • Figure 0007602369000004
    Figure 0007602369000004
  • Figure 0007602369000005
    Figure 0007602369000005
Patent Text Reader

Abstract

To provide an impurity analysis method for performing a chemical analysis of impurities on an outer surface of an analysis object nondestructively, and to provide a liquid chemical collection container used for the same.SOLUTION: An impurity analysis method includes steps of: using an etching solution E, filling the inside of a liquid chemical container 10 with the etching solution E, and allowing the etching solution to protrude from an upper end of the liquid chemical container by surface tension (Fig. 4(a)); pressing the liquid chemical container 10 against an outer surface of an analysis object 1 while the etching solution E protrudes from an upper end of the liquid chemical container 10 (Fig. 4(b)); dissolving the outer surface of the analysis object 1 by the etching solution E by maintaining the pressed state (Fig. 4(b)); collecting the etching solution E for dissolving the outer surface; and analyzing impurities on the outer surface of the analysis object 1.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an impurity analysis method and a chemical container used therefor, and more particularly to an impurity analysis method suitable for analyzing impurities on the outer surface of a silica glass crucible used for pulling silicon single crystals, and a chemical container used therefor. [Background technology]

[0002] For example, in the manufacture of semiconductor wafers, a silica glass crucible is used as a quartz glass member when pulling up a silicon single crystal. This silica glass crucible is used for processing in a high-temperature environment, where polycrystalline silicon is stored, heated and melted, and silicon single crystal is grown and pulled up. The silica glass crucible used for this purpose is formed with high purity to prevent impurities from being mixed into the silicon single crystal being pulled up, and is also highly durable and heat resistant, since it is used in processing in a high-temperature environment.

[0003] Incidentally, in the process of melting polycrystalline silicon and pulling up a silicon single crystal, the inner surface of the silica glass crucible is gradually dissolved by the silicon melt. Therefore, when the impurity concentration (especially the concentration of metal impurities such as Fe and Cu) on the inner surface of the silica glass crucible is high, the impurities contained in the molten glass can mix with the silicon single crystals and have a negative effect on the silicon wafers, leading to reduced product yields and deterioration in quality. Therefore, in order to ensure the purity of the inner surface of the silica glass crucible, chemical analysis etc. may be performed on the inner surface.

[0004] As a chemical analysis of this inner surface, Patent Document 1 proposes a method in which hydrofluoric acid vapor is brought into contact with the inner surface of a sealed quartz crucible, and then the inner surface is washed with pure water to remove impurities, and the washing liquid is then recovered and analyzed.

[0005] In addition, Patent Document 2 proposes that a tool for collecting impurities from a quartz crucible is placed on the surface of a crucible sample cut out from an arbitrary position of the quartz crucible, a storage space for an etching solution is formed on the surface of the crucible sample, and the etching solution is introduced into the storage space.The etching solution is then allowed to come into contact with the crucible for a predetermined period of time, and then the etching solution is collected and the metal impurity concentration on the inner surface of the quartz crucible is analyzed. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 5-105574 [Patent Document 2] JP 2019-66262 A Summary of the Invention [Problem to be solved by the invention]

[0007] As described above, the inner surface of the silica glass crucible needs to be kept highly pure. However, even if the inner surface of the silica glass crucible is continuously kept highly pure, the quality of the silicon single crystal may deteriorate. This is thought to be due to the purity of the outer surface of the silica glass crucible, but there was a problem in that a method for chemical analysis of the purity of the outer surface had not been established. In other words, analysis of the outer surface of the silica glass crucible requires the use of chemical agents to investigate the outside of the bowl shape (curved shape), which makes it more difficult than analysis of the inner surface, such as methods for recovering the chemicals and controlling the diffusion of the chemicals onto the outer surface. Here, diffusion of the chemical onto the outer surface refers to the phenomenon in which the chemical spreads over the outer surface and penetrates into the outer surface due to capillary action through tiny cracks and irregularities present on the outer surface of the silica glass crucible.

[0008] Furthermore, analysis of the outer surface of the silica glass crucible must be performed non-destructively in order to ensure its usability as a silica glass crucible. The chemical analysis method disclosed in Patent Document 1 satisfies the above requirements because it is a non-destructive method for confirming purity results. However, it is difficult to seal the outer surface of the silica glass crucible, and furthermore, it is difficult to bring hydrofluoric acid vapor into contact with the outer surface of the silica glass crucible. Therefore, it is difficult to apply the chemical analysis method shown in Patent Document 1 to a method for chemically analyzing the outer surface of a silica glass crucible.

[0009] In addition, the chemical analysis method shown in Patent Document 2 involves cutting a sample to a size suitable for chemical analysis from a silica glass crucible, contacting the outer surface of the sample with an etching solution, recovering the etching solution, and analyzing the metal impurity concentration on the outer surface of the silica glass crucible. Therefore, this method does not satisfy the requirement for non-destructive analysis. Furthermore, when cutting out a sample from a silica glass crucible, there was a risk of contamination of the cutter used for cutting, or of impurities being mixed in when handling the sample after cutting, making it impossible to perform a high-precision analysis.

[0010] Furthermore, in addition to silica glass crucibles, there is also a demand for chemical analysis of impurities on the outer surface of large transparent quartz glass members with distorted shapes, for example.Furnace core tubes may also be made of silicon carbide ceramics other than quartz glass, and it is desirable to chemically analyze the impurities on the outer surface of these as well.

[0011] The present invention has been made to solve the above-mentioned technical problems, and has an object to provide an impurity analysis method for non-destructively chemically analyzing impurities on the outer surface of an object, and a chemical liquid container for use therein. [Means for solving the problem]

[0012] The impurity analysis method of the present invention, which has been made to achieve the above-mentioned object, is a method for non-destructive chemical analysis of impurities on the outer surface of an object, and is characterized by including the steps of: using an etching solution, filling a chemical solution container with the etching solution and causing the etching solution to protrude from an upper end of the chemical solution container due to surface tension; pressing the chemical solution container against the outer surface of the object while the etching solution protrudes from the upper end of the chemical solution container; maintaining the pressed state so that the etching solution dissolves the outer surface of the object; recovering the etching solution that has dissolved the outer surface; and analyzing the impurities on the outer surface.

[0013] In this way, in the present invention, the chemical container is pressed against the outer surface of the object with the etching solution protruding from the upper end of the container, and the outer surface of the object is dissolved by the etching solution.The etching solution that has dissolved the outer surface of the object is then recovered and analyzed for impurities. Therefore, impurities on the outer surface of the object can be non-destructively chemically analyzed. In particular, since the chemical container is pressed against the outer surface of the object with the etching solution protruding from the upper end of the container, the outer surface of the object can be dissolved by the etching solution even if the outer surface of the object has a curved surface, and impurities can be analyzed.

[0014] Here, it is preferable that the object is a silica glass crucible. However, the method can be applied to other objects than a silica glass crucible, such as a large transparent quartz glass member having a distorted shape, a furnace core tube made of silicon carbide, and the like, for example.

[0015] The etching solution is preferably an etching solution containing hydrofluoric acid. As the etching solution, other than hydrofluoric acid, for example, aqua regia, nitric acid, etc. can be used.

[0016] Furthermore, when the inner diameter of the silica glass crucible is less than 30 inches, 50 ml or less of an etching solution having a hydrofluoric acid concentration of 20 wt % or more and 30 wt % or less should be used, and when the inner diameter of the silica glass crucible is 30 inches or more, 100 ml or less of an etching solution having a hydrofluoric acid concentration of 20 wt % or more and 30 wt % or less should be used, and it is desirable that the etching time be 60 minutes or less.

[0017] In addition, in order to achieve the above-mentioned object, the chemical liquid container used in the impurity analysis method of the present invention is characterized by comprising a bottomed cylindrical chemical liquid storage section, and a bottomed cylindrical chemical liquid recovery section arranged so that the chemical liquid storage section is located at the center. Effect of the Invention

[0018] According to the present invention, it is possible to obtain an impurity analysis method for non-destructively chemically analyzing impurities on the outer surface of an object, and a chemical container for use therein. [Brief description of the drawings]

[0019] [Figure 1] 1 is a perspective view showing one embodiment of a drug solution container according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of FIG. [Diagram 3] 1 is a schematic cross-sectional view showing a configuration of a mounting table used in one embodiment of an impurity analysis method according to the present invention. [Figure 4] 1 is a schematic diagram for explaining one embodiment of the impurity analysis method according to the present invention, in which (a) is a diagram showing a process of bringing the chemical solution container close to the outer surface of a quartz glass member with the etching solution protruding from the upper end of the container, and (b) is a diagram showing a process of pressing the chemical solution container against the outer surface of the quartz glass member and dissolving the outer surface of the quartz glass member with the etching solution. [Diagram 5] FIG. 5 is a schematic cross-sectional view illustrating a method for analyzing impurities on the outer surface of a quartz glass member different from that in FIG. 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] An embodiment of an impurity analysis method and a chemical container used therein according to the present invention will be described with reference to Figures 1 to 4. First, an embodiment of a chemical container used in this impurity analysis method will be described with reference to Figure 1.

[0021] As shown in FIG. 1, the drug solution container 10 includes a bottomed, cylindrical drug solution storage section 11 in which the drug solution E is stored, and a bottomed, cylindrical drug solution recovery section 12 arranged so that the drug solution storage section 11 is located in the center and which recovers the drug solution E that has overflowed from the drug solution storage section 11. The chemical solution container 10 is made of a material having chemical resistance in order to store an etching solution for etching the object of analysis. As the etching solution, other than hydrofluoric acid, for example, aqua regia, nitric acid, etc. can be used. For example, when the object to be analyzed is a quartz glass member and the etching solution is an etching solution containing hydrofluoric acid, the chemical solution container 10 does not need to be made of glass similar to the quartz glass member to be analyzed, but can be made of polyvinyl chloride or fluororesin. Furthermore, if the subject of analysis is a quartz glass member and the liquid medicine container 10 is made of the same glass as the quartz glass member to be analyzed, there is a risk of damaging the quartz glass member when the liquid medicine container 10 comes into contact with the outer surface of the quartz glass member, which is not preferable. On the other hand, if the liquid medicine container 10 is made of polyvinyl chloride or fluororesin, it is preferable because it is less likely to damage the quartz glass member to be analyzed.

[0022] The height H of the side wall 11 a of the liquid drug storage section 11 of the liquid drug container 10 is formed to be higher than the height h of the side wall 12 a of the liquid drug recovery section 12 . In this way, the height H of side wall 11a of drug solution storage section 11 is made higher than the height h of side wall 12a of drug solution recovery section 12 in order to prevent a situation where, when drug solution container 10 is brought into contact with the outer surface of the object to be analyzed, the upper end of side wall 12a of drug solution recovery section 12 comes into contact with the outer peripheral surface of the object to be analyzed, thereby preventing the upper end of side wall 11a of drug solution storage section 11 from being unable to come into contact with the outer surface of the object to be analyzed.

[0023] Moreover, the liquid medicine storage section 11 and the liquid medicine recovery section 12 of the liquid medicine container 10 are formed in a circular shape in a plan view, and the inner diameter D of the liquid medicine storage section 11 is formed smaller than the inner diameter d of the liquid medicine recovery section 12. When the etching solution E stored in the chemical solution storage section 11 comes into contact with the outer surface of the object to be analyzed, the etching solution E overflows from the chemical solution storage section 11. Then, the etching solution E is collected in the chemical solution collection section 12 provided so as to surround the chemical solution storage section 11. Therefore, chemical liquid recovery section 12 is formed with an inner diameter d and a height h capable of containing the etching liquid overflowing from chemical liquid storage section 11.

[0024] In addition, since the etching solution protrudes from the upper end of the chemical solution container due to surface tension, it is preferable that the inner diameter D of the chemical solution storage section 11 of the chemical solution container 10 is small. In addition, by making the inner diameter D small, impurities in a small area on the outer surface of the analysis target can be analyzed.

[0025] As a specific example, the height H of side wall 11a of drug solution storage section 11 of drug solution container 10 is 40 mm to 60 mm, the height h of side wall 12a of drug solution recovery section 12 is 20 mm to 40 mm, the inner diameter D of drug solution storage section 11 is 40 mm to 50 mm, and the inner diameter d of drug solution recovery section 12 is 50 mm to 100 mm. It is also preferable that the thickness T of the side wall 11a of the drug solution storage section 11 is 2 mm to 3 mm, and the thickness t of the side wall 12a of the drug solution recovery section 12 is 2 mm to 3 mm.

[0026] Next, an embodiment of the impurity analysis method according to the present invention will be described with reference to FIGS. This impurity analysis method is a method for non-destructively chemically analyzing impurities on the outer surface of an object to be analyzed, using the above-mentioned chemical solution container 10. Here, a description will be given of a silica glass crucible (quartz glass member) as an example of the object to be analyzed.

[0027] 3, the silica glass crucible 1 is placed on a mounting table 2. An opening 2a is formed in the bottom surface of the mounting table 2. Meanwhile, the chemical container 10 is placed on a lifting table 3, and the lifting table 3 moves the chemical container 10 into the opening 2a from below the mounting table 2 and into contact with the outer surface of the silica glass crucible 1.

[0028] In the impurity analysis, the storage portion 11 of the chemical container 10 is filled with the etching solution, and the etching solution E is caused to protrude from the upper end of the side wall 11a of the chemical container 10 due to surface tension. Here, the etching solution may be aqua regia or nitric acid. In particular, since the purpose is to dissolve the silica glass crucible, it is preferable that the etching solution contains hydrofluoric acid.

[0029] The concentration of hydrofluoric acid is preferably 20 wt % or more and 30 wt % or less. Glass surfaces are more easily wetted by hydrofluoric acid than by pure water, and naturally the higher the concentration of hydrofluoric acid, the greater the wettability of the glass surface. On the other hand, the lower the concentration of hydrofluoric acid, the lower the wettability and the easier it is to recover, but low concentrations of hydrofluoric acid make etching take longer and difficult in the first place. If the concentration of hydrofluoric acid is less than 20 wt %, the amount of the outer surface of the quartz glass member (the silica glass crucible 1) that dissolves is small, and the dissolution takes a long time, which is undesirable. On the other hand, if the concentration of hydrofluoric acid exceeds 30 wt %, the outer surface of the quartz glass member (silica glass crucible 1) becomes easily wetted, diffusion to the outer surface becomes large, and recovery becomes difficult, which is undesirable.

[0030] Then, as shown in Figure 4(a), with the etching solution E protruding from the upper end of the chemical solution container 10, the chemical solution container 10 (lifting platform 3) is raised, and the chemical solution recovery container 10 enters through the opening 2a on the bottom surface of the mounting platform 2 and is brought into contact with and pressed against the outer surface of the bottom portion 1a of the silica glass crucible 1. When the chemical solution container 10 is brought into contact with and pressed against the outer surface of the bottom portion 1a of the silica glass crucible 1, as shown in Figure 4(b), the etching solution protruding from the upper end of the chemical solution container overflows from the storage portion 11 of the chemical solution container 10 and is collected in the recovery portion 12.

[0031] Then, the outer surface is dissolved by the etching solution by keeping the chemical container 10 pressed against the outer peripheral surface of the bottom portion 1a of the silica glass crucible 1. By keeping the pressed state for the time required for dissolution, etching with the chemical solution is performed to a desired depth. For example, to etch the outer surface of the bottom portion 1a of the silica glass crucible 1 to a depth of 10 to 40 μm, the time for which this pressing state is maintained varies depending on the concentration of the etching solution. When the concentration of hydrofluoric acid is 20 wt% or more and 30 wt% or less, the etching time is set to 20 minutes or more and 60 minutes or less. In addition, the amount of chemical solution used can be limited to 50 ml or less if the diameter of the silica glass crucible is less than 30 inches, and to 100 ml or less if the diameter is 30 inches or more, and the etching time can be set to 60 minutes or less, thereby controlling the diffusion of chemicals into the outer surface of the silica glass crucible.

[0032] By varying the chemical concentration and contact time, it is also possible to examine the degree of contamination by impurities in the depth (thickness) direction of an etching depth of 40 μm or more.

[0033] Then, the chemical container 10 is pressed against the outer peripheral surface of the bottom portion 1a of the silica glass crucible 1 for a predetermined time, and then the etching solution that has dissolved the outer surface is collected. In this recovery of the etching solution, the etching solution stored in the chemical solution reservoir 11 of the chemical solution container 10 is recovered.

[0034] Next, the collected etching solution is analyzed for impurities by a commonly known method. For example, the analysis method may be ICP-MS (inductively coupled plasma mass spectrometry), ICP-AES (inductively coupled plasma atomic emission spectrometry), or AAS (atomic absorption spectrometry). By collecting and analyzing this etching solution, the degree of contamination of the outer surface of the silica glass crucible by impurities can be known.

[0035] As described above, according to the impurity analysis method of the present invention, the purity of the outer surface (in other words, the degree of impurity contamination) of the silica glass crucible (object to be analyzed) can be known without destroying the silica glass crucible (object to be analyzed), and if the purity of the inner surface is also known by conventional methods, the purity (degree of impurity contamination) of the entire silica glass crucible (object to be analyzed) can be confirmed and guaranteed. In other words, the purity of the silica glass crucible can be guaranteed not only by the purity of the inner surface that comes into direct contact with the silicon melt, but also by non-destructive chemical analysis of the outer surface of the silica glass crucible, so the analytical purity of the entire silica glass crucible can be confirmed in advance.

[0036] In the above embodiment, impurity analysis was performed on the bottom surface 1a (curved surface) of the silica glass crucible, but impurity analysis can also be performed on the outer surface of the body portion 1b (straight portion) of the silica glass crucible 1, as shown in Figure 5. In addition, in the above embodiment, a silica glass crucible (quartz glass member) is used as an example of the object to be analyzed, but the present invention is not limited to this and can be applied to other objects to be analyzed. EXAMPLES

[0037] Example 1 In Example 1, the bottom surface of a 28-inch diameter silica glass crucible was etched with 50 ml of 30 wt % hydrofluoric acid solution for 25 minutes. The results of the outer surface analysis are shown in Table 1.

[0038] Example 2 In Example 2, the bottom surface of a 28-inch diameter silica glass crucible was etched for 20 minutes using 40 ml of a 25 wt % hydrofluoric acid solution. The results of the outer surface analysis are shown in Table 1.

[0039] Example 3 As Example 1, the bottom surface of a 28-inch diameter silica glass crucible was etched with 45 ml of 20 wt % hydrofluoric acid solution for 30 minutes. The results of the outer surface analysis are shown in Table 1.

[0040] (Reference example 1) As Reference Example 1, the bottom surface of a 28-inch diameter silica glass crucible similar to that of Example 1 was used, and the results of the outer surface analysis when 20 ml of a 25 wt % hydrofluoric acid solution was used for etching for 25 minutes are shown in Table 1.

[0041] (Reference example 2) As Reference Example 2, the bottom surface of a 28-inch diameter silica glass crucible was used, and the results of the outer surface analysis when 50 ml of a 25 wt % hydrofluoric acid solution was used and the etching time was 5 minutes are shown in Table 1.

[0042] (Reference example 3) As Reference Example 3, the bottom surface of a 28-inch diameter silica glass crucible was used, and the results of the outer surface analysis when 50 ml of a 10 wt % hydrofluoric acid solution was used for etching for 10 minutes are shown in Table 1.

[0043] (Reference example 4) As Reference Example 4, the bottom surface of a 28-inch diameter silica glass crucible was etched for 20 minutes using 55 ml of 35 wt % hydrofluoric acid solution. The results of the outer surface analysis are shown in Table 1.

[0044] [Table 1]

[0045] In the cases of Examples 1 to 3, the hydrofluoric acid diffused onto the outer surface of the bottom portion of the silica glass crucible, and the amount of hydrofluoric acid required for analysis could be recovered, so that the evaluation was "fair." In the case of Reference Example 1, the amount of hydrofluoric acid used was small, so that the hydrofluoric acid diffused onto the outer surface of the bottom part of the silica glass crucible, and the amount required for analysis could not be recovered, and therefore the evaluation was "Fail." In the case of Reference Example 2, the etching time was as short as 5 minutes, and etching of the outer surface of the bottom part of the silica glass crucible was insufficient, making it impossible to obtain precise analysis results, and therefore the evaluation was "fail."

[0046] In the case of Reference Example 3, when the hydrofluoric acid concentration was low at 10 wt% and the etching time was relatively short at 10 minutes, the amount of etching was small, as in Reference Example 2, and precise analysis results could not be obtained for the outer surface of the bottom portion of the silica glass crucible, so the evaluation was "Fail." In the case of Reference Example 4, because a large amount of hydrofluoric acid was used, the hydrofluoric acid diffused too much onto the outer surface of the bottom part of the silica glass crucible, resulting in a lot of noise. In addition, because the hydrofluoric acid concentration was high at 35 wt%, and the etching time was also 20 minutes, the amount of etching was large, and it was not possible to obtain precise analysis results for the outer surface of the bottom part of the silica glass crucible, so the evaluation was "Fail."

[0047] Example 4 In Example 4, the bottom surface of a 30-inch diameter silica glass crucible was etched for 25 minutes using 100 ml of 30 wt % hydrofluoric acid solution. The results of the outer surface analysis are shown in Table 2.

[0048] Example 5 In Example 5, the bottom surface of a 30-inch diameter silica glass crucible was etched with 80 ml of 25 wt % hydrofluoric acid solution for 20 minutes. The results of the outer surface analysis are shown in Table 2.

[0049] Example 6 As Example 6, the bottom surface of a 30-inch diameter silica glass crucible was etched for 30 minutes using 60 ml of a 20 wt % hydrofluoric acid solution. The results of the outer surface analysis are shown in Table 2.

[0050] (Reference example 5) As Reference Example 5, the bottom surface of a 30-inch diameter silica glass crucible similar to that of Example 4 was used, and the results of the outer surface analysis when etching was performed for 25 minutes using 40 ml of 25 wt % hydrofluoric acid solution are shown in Table 2.

[0051] (Reference example 6) As Reference Example 6, the bottom surface of a 30-inch diameter silica glass crucible was used, and the results of the outer surface analysis when 100 ml of a 25 wt % hydrofluoric acid solution was used and the etching time was 5 minutes are shown in Table 2.

[0052] (Reference example 7) As Reference Example 7, the bottom surface of a 30-inch diameter silica glass crucible was used, and the results of the outer surface analysis when 100 ml of a 10 wt % hydrofluoric acid solution was used for etching for 10 minutes are shown in Table 2.

[0053] (Reference example 8) As Reference Example 8, the bottom surface of a 30-inch diameter silica glass crucible was used, and the results of the outer surface analysis when 110 ml of a 35 wt % hydrofluoric acid solution was used for etching for 20 minutes are shown in Table 2.

[0054] [Table 2]

[0055] In the cases of Examples 4 to 6, the hydrofluoric acid diffused onto the outer surface of the bottom portion of the silica glass crucible, and the amount of hydrofluoric acid required for analysis could be recovered, so that the evaluation was "fair." In the case of Reference Example 5, the amount of hydrofluoric acid used was small, so that the hydrofluoric acid diffused onto the outer surface of the bottom part of the silica glass crucible, and it was not possible to recover the amount required for analysis, and therefore the evaluation was "Fail." In the case of Reference Example 6, the etching time was as short as 5 minutes, and etching of the outer surface of the bottom part of the silica glass crucible was insufficient, making it impossible to obtain precise analysis results, and therefore the evaluation was "fail."

[0056] In the case of Reference Example 7, when the hydrofluoric acid concentration was low at 10 wt% and the etching time was relatively short at 10 minutes, the amount of etching was small, as in Reference Example 6, and precise analysis results could not be obtained for the outer surface of the bottom portion of the silica glass crucible, so the evaluation was "Fail." In the case of Reference Example 8, because a large amount of hydrofluoric acid was used, the hydrofluoric acid diffused too much onto the outer surface of the bottom part of the silica glass crucible, resulting in a lot of noise. In addition, because the hydrofluoric acid concentration was high at 35 wt%, and the etching time was also 20 minutes, the amount of etching was large, and it was not possible to obtain precise analysis results for the outer surface of the bottom part of the silica glass crucible, so the evaluation was "Fail."

[0057] In view of the above, when performing an outer surface analysis, in the case of a 28-inch diameter silica glass crucible, i.e., a silica glass crucible with a diameter of less than 30 inches, it is desirable that the hydrofluoric acid concentration be 20 wt% or more and 30 wt% or less, the amount of hydrofluoric acid used be 40 ml or more and 50 ml or less, and the etching time be 20 minutes or more and 30 minutes or less. In addition, in the case of a silica glass crucible with a diameter of 30 inches or more, it is desirable that the hydrofluoric acid concentration be 20 wt% or more and 30 wt% or less, the amount of hydrofluoric acid used be 60 ml or more and 100 ml or less, and the etching time be 20 minutes or more and 30 minutes or less. [Explanation of symbols]

[0058] 1. Silica glass crucible (quartz glass material, analysis target) 2. Placement table 2a opening 3 Lifting platform 10. Chemical container 11. Drug storage section 12 Chemical recovery section E Etching solution (chemical solution)

Claims

1. 1. A method for non-destructively chemically analyzing impurities on an outer surface of an object, comprising: A step of filling an etching solution into a chemical container with the etching solution and protruding the etching solution from an upper end of the chemical container by surface tension; pressing the chemical container against an outer surface of an object with the etching solution protruding from an upper end of the chemical container; maintaining the pressure so that the etching solution dissolves the outer surface of the object; recovering the etching solution that has dissolved the exterior surface; analyzing the exterior surface for impurities; 2. A method for analyzing impurities comprising:

2. 2. The method for analyzing impurities according to claim 1, wherein the object is a silica glass crucible.

3. 3. The method for analyzing impurities according to claim 1, wherein the etching solution contains hydrofluoric acid.

4. When the inner diameter of the silica glass crucible is less than 30 inches, use 50 ml or less of an etching solution having a hydrofluoric acid concentration of 20 wt % or more and 30 wt % or less; When the inner diameter of the silica glass crucible is 30 inches or more, use 100 ml or less of an etching solution having a hydrofluoric acid concentration of 20 wt % or more and 30 wt % or less; 3. The method for analyzing impurities according to claim 2, wherein the etching time is 60 minutes or less.

5. A chemical solution container for use in the impurity analysis method according to any one of claims 1 to 4, A cylindrical drug solution storage portion with a bottom; A cylindrical drug solution recovery section with a bottom, the drug solution storage section being arranged so as to be located at a center portion thereof; wherein a height of a side wall of the liquid medicine storage section is greater than a height of a side wall of the liquid medicine recovery section.

Citation Information

Patent Citations

  • Cleaning and recovery of impurity on inner surface of quartz crucible

    JP1993105574A

  • Method and apparatus for forming thin film sample

    JP1995043277A

  • Container for recovering metal and method for recovering metal

    JP1998064966A

  • Method and device for preparing sample for x-ray analysis

    JP1999160208A

  • Method and apparatus for evaluating periphery of semiconductor wafer

    JP2000077492A